Valuing the Global Mortality Consequences of Climate Change Accounting for Adaptation Costs and Benefits. Issue 4 (21st April 2022) - Carleton, Tamma; Jina, Amir; Delgado, Michael; Greenstone, Michael; Houser, Trevor; Hsiang, Solomon; Hultgren, Andrew; Kopp, Robert E; McCusker, Kelly E; Nath, Ishan; Rising, James; Rode, Ashwin; et al.
Abstract: Using 40 countries' subnational data, we estimate age-specific mortality-temperature relationships and extrapolate them to countries without data today and into a future with climate change. We uncover a U-shaped relationship where extre6me cold and hot temperatures increase mortality rates, especially for the elderly. Critically, this relationship is flattened by higher incomes and adaptation to local climate. Using a revealed-preference approach to recover unobserved adaptation costs, we estimate that the mean global increase in mortality risk due to climate change, accounting for adaptation benefits and costs, is valued at roughly 3.2% of global GDP in 2100 under a high-emissions scenario. Notably, today's cold locations are projected to benefit, while today's poor and hot locations have large projected damages. Finally, our central estimates indicate that the release of an additional ton of CO2 today will cause mortality-related damages of 36.6 under a high-emissions scenario, with an interquartile range accounting for both econometric and climate uncertainty of [−7.8, 73.0]. These empirically grounded estimates exceed the previous literature's estimates by an order of magnitude.